Trends and disparity in the provision and consumption of essential medicines in China from 2016 to 2021: institutional, regional, and economic variations - Zhao, Mingyue; Lin, Chenglong; Ding, Shengjie; Han, Yubei; Zhao, Yuhan; Gillani, Ali Hassen; Fang, Yu (Frontiers in Public Health, 2025)
ObjectiveAnalyze the provision and consumption of essential medicines (EMs) across healthcare institutions, regions, and levels of economic development. Evaluate the mechanisms by which EMs policies promote their own implementation.MethodsUsing national drug utilization monitoring database (2016–2021), we perform a descriptive analysis to explore trends and disparities in EM provision and consumption across three institution levels, four regions (from 30 provinces), and different economic development levels in China. Key metrics include the average number and proportion of provided EMs and the consumption rate per healthcare institution. Utilize a two-way fixed-effects regression model to evaluate the relationship between EMs provision and consumption.FindingsThe average provided number of EMs is much lower than that in the national EMs list. Both provision (number and proportion) and consumption of EMs show institutional and regional disparities. There is a moderately positive correlation between EMs provided proportion and GDP (0.66, p < 0.01), while the provided proportion and consumption rate are moderately negatively correlated with GDP (−0.66, p < 0.01; −0.64, p < 0.01). In highly developed regions, EMs supply is highest but utilization lowest; in underdeveloped regions, provision is least but utilization relatively high.ConclusionThis study shows disparities in EM provision and consumption across institutions, regions, and economic levels in China. Although essential medicine policy coordination with other policies needs improvement, targeted interventions are needed to bridge gaps in less developed regions and promote medicine equity.